Clinical characteristics and outcomes of patients on haemodialysis at Jimma medical center, Ethiopia: a 7-Year review - Sisay Tagese Tafese; Eyob Girma Abera; Meron Debebe Mersha; Maekel Belay Woldemariam (BMC Nephrology)
Abstract Background Haemodialysis is the primary kidney replacement therapy modality in Africa. In Ethiopia, the number of patients undergoing Haemodialysis is increasing, yet data on their outcomes is scarce. This study assesses the clinical characteristics and outcomes of Haemodialysis patients at Jimma Medical Center. Methods A retrospective cross-sectional study was conducted from April 08 to 12, 2024, involving patients who underwent Haemodialysis at Jimma Medical Center from June 2017 to March 2024. The data were coded and entered into EpiData version 3.1, then exported to the Statistical Package for Social Sciences version 26.0 for analysis. Descriptive statistics summarized the patients’ clinical characteristics and outcomes, and Kaplan-Meier curves were used to assess survival status. Results During the seven-year study period, 68 patients underwent Haemodialysis at Jimma Medical Center, with a predominance of males (69.1%). The average age of patients was 42.7 (± 12.8) years with 69.1% (95% CI: 57.5–79.1%) diagnosed with chronic kidney disease, while 30.9% (95% CI: 20.9–42.5%) had acute kidney injury. Among chronic kidney disease patients, common clinical features included nausea and vomiting (100%), proteinuria (95.7%), and body swelling (82.9%), while acute kidney injury patients frequently presented with oliguria (100%), nausea and vomiting (90.5%), and hematuria (52.4%). Hypertensive nephropathy was the leading cause of chronic kidney disease (40.4%), and acute glomerulonephritis (38.1%) and severe malaria (33.3%) were the predominant causes of acute kidney injury. Mortality was observed at 47.6% (95% CI: 27.7–68.6%) in acute kidney injury patients and 40.4% (95% CI: 27.3–54.7%) in chronic kidney disease patients. Emergency vascular access was required in 95.7% of chronic kidney disease and 100% of acute kidney injury patients. Conclusion This study highlights the substantial burden of chronic kidney disease and acute kidney injury among hemodialysis patients at Jimma Medical Center, revealing distinct clinical profiles and outcomes. Although acute kidney injury patients exhibited a longer median survival time, the significant mortality risk within the first year underscores the urgent need for improved treatment access and resource allocation. Enhancing early intervention and ensuring the availability of critical medications, such as erythropoietin, are essential for optimizing patient outcomes for both chronic kidney disease and acute kidney injury groups. Clinical trial number:Not applicable